A dimensão social dos direitos humanos: estudo para a reconstituição dos fundamentos éticos dos direitos sociais - Flinkerbusch, Alcides Otto (Universidade do Vale do Rio do Sinos, 2006)
This paper is about the foundations of social rights, considering them as one of the dimensions of human rights. The study has used the literature review method and is divided into three parts. The first part presents the history of human rights standardization worldwide, involving the materialization of civil and political rights (freedom rights) and of economic, social and cultural rights (equality rights). Next, the theoretical foundations of human rights are discussed. Here, an analysis of the theoretical limitations of natural law and legal positivism in their attempt to justify the universalization of human rights is made; it is, additionally, about building the idea of human dignity as a consequence of ethical foundation, resorting to Immanuel Kant’s moral philosophy; and, based on these assumptions, the bases of the ethical foundations of social rights as imperatives of the Democratic Rule of Law are recovered. It is about the debate on the arguments used as theoretical barriers in the materialization
Keywords: dignidade humana; direitos sociais; direitos humanos; foundation; social rights; human rights; Ciências Sociais Aplicadas